An investigation into the nature and adequacy of tax compliance tools available to assist small businesses in the state of Oklahoma in the United States of America - Cary, Cindi L (Rhodes University, Faculty of Commerce, Department of Accounting, 2020)
This study identifies and analyses the effectiveness of the tax tools available to the small businesses that make up more than 99 per cent of all businesses in the United States and the state of Oklahoma through an extensive investigation of the small business resources offered by federal and state government agencies, higher education institutions and the professional accounting community. The study uses numerous measurements in order to acquire multiple perspectives and relies on the examination of government websites and documents, interviews, experiments, surveys, and questionnaires to determine the existing small business tax tools and their limitations. The research offers an in-depth analysis of the facts and limitations of the small business services offered by the Internal Revenue Service (IRS). The IRS is determined the largest source of small business tax tools, but limitations plague their effectiveness. Higher education is found guilty of not providing small business education in business or accounting disciplines, leaving college graduates ill-prepared to assist small businesses. Higher education is urged to implement a small business accounting curriculum that couples field experience with classroom lectures and textbooks. This study finds the accounting profession apathetic with regard to informing small businesses of accounting services and presses certified public accountants to be more involved in the education of future small business accountants. The study concludes with recommendations to reduce the small business tax burden by improving the existing small business tax tools.
Keywords: Tax administration and procedure -- United States; United States. Internal Revenue Service; Small business -- Oklahoma; Small business -- United States; Taxpayer compliance -- Oklahoma; Taxpayer compliance -- United States